Studies of interactions of STIM1 and GPCRs with their binding partners - How, Jonathan Guan Zhong (2015)
Membrane proteins are responsible for cellular functions such as cell signalling and ion transport. Almost half of all modern medicinal drugs have membrane proteins as their targets. In this thesis, focus is on two transmembrane proteins: Adenosine A2A receptor (A2aR) as a model for G-protein coupled receptors (GPCRs) and stromal interacting molecule 1 (STIM1). GPCRs interact with extracellular compounds that activate cellular signalling pathways, leading to the generation of a large variety of cellular responses. Down the signalling pathway is the calcium release-activated calcium (CRAC) channel that consists of the ER embedded STIM1 and the plasma membrane embedded Orai1. Together, these proteins are involved in the regulation of intracellular Ca2+ levels that are essential for immune system response. The nature of these membrane proteins has made their expression and purification difficult. In this study, methods were introduced which helped to improve the stability and expression of both GPCR and STIM1 with minimal mutation of residues. A2aR was incorporated into nanodiscs to improve its stability. Expression assays were performed in conjunction with thermo-stability and oligomerization assays to identify the regions of STIM1 necessary for good expression and stability. This was followed by the optimization of SPR binding assays and the determination of the affinity values for the interaction between (a) A2aR and their ligands; and (b) STIM1 and Orai1 N- and C- termini. Additionally, the first coiled-coil domain of STIM1 was found to be involved in the interaction of STIM1with Orai1, suggesting its potential role as a docking site for Orai1. The kinetic constants of the interaction between A2aR and its agonists were determined. The SPR assays developed within this project will be useful for the analysis of interactions between other GPCRs and their binders.